Studies of the laser thermal probe in cardiovascular disease - Rosenthal, Eric (Division of Cardiology, 2017)
The initial use of optical fibres to transmit laser energy intravascularly was accompanied by a high rate of perforations and the production of inadequate vascular channels when used for recanalisation. The laser thermal probe - in which all laser energy is converted into heat by a metal cap at the tip of the fibre, prior to tissue application - was one of the earliest modifications designed to overcome these problems. The studies in this thesis were concerned with the application of the laser thermal probe to percutaneous peripheral and coronary artery angioplasty and His bundle ablation. In vitro studies were commenced in March 1987 when the first (argon) laser generator was installed in the cardiac catheterisation laboratory at Guy's Hospital and these were followed by clinical studies in three groups of patients: nine with peripheral artery occlusions, three with coronary artery stenoses and four with supraventricular arrhythmias using either argon or Nd-YAG energies. Suggestions that enhanced safety might be possible with on-line monitoring and/or control of the probe temperature were studied by recording the temperature responses in simulated circulations at flow rates observed clinically. The highly variable temperatures recorded in blood indicate that these measures are unlikely to contribute to improvements in either efficacy or clinical safety. An earlier report of successful peripheral artery recanalisation using the laser thermal probe was confirmed in the patients studied here, though a learning curve was evident. Coronary laser angioplasty had also been performed in a few patients with a similar device but without as much success. A more flexible "over the wire" laser probe was assessed here, first in cadaver coronary arteries and then in three patients undergoing coronary angioplasty. The lack of success seen with this laser thermal probe relates to the considerable differences found between peripheral and coronary arteries: percutaneous accessibility, vessel size and the susceptibility to thermal injury being the most important. These aspects and subsequent developments in coronary laser angioplasty are discussed further. The final chapter considers a hitherto new area for laser thermal probe application the interruption of arrhythmia circuits. Cadaver and electrophysiological studies indicated that ablation of the bundle of His might be possible with this device - without the need for a general anaesthetic. The course of the first patient ever to undergo this procedure is described, as well as the implications for percutaneous His bundle ablation using other energy sources.